A wall-less Tissue Equivalent Proportional Counter as connecting bridge from microdosimetry to nanodosimetry. (June 2020) - Mazzucconi, D.; Bortot, D.; Rodriguez, P. Martin; Pola, A.; Fazzi, A.; Colautti, P.; Conte, V.; Selva, A.; Agosteo, S.
Abstract: The deep understanding of the interaction between ionizing radiation and soft tissue is of fundamental for radiotherapy and hadron therapy. The complexity of the damage caused by radiation and its biological effectiveness depends on the structure of particles track at the scale of subcellular targets, of the order of some nanometers. Microdosimetry and track-nanodosimetry provide the methodologies and tools to describe and comprehend this phenomenon and optimize the therapy. A novel wall-less avalanche-confinement Tissue Equivalent Proportional Counter (TEPC) designed for simulating nanometric sites down to 25 nm was constructed. This range of operation provides the means to perform the direct comparison between microdosimetric spectra and track-nanodosimetric distributions acquired by STARTRACK nanodosimeter at the INFN-LNL. The novel TEPC has been characterized employing an 241 Am alpha source for both determining the best operation conditions in terms of voltages applied to the electrodes in the range 100 – 25 nm and analyzing its response down to the nanometric region. The nano-microdosimeter was able to measure alpha spectra down to 25 nm. The gas gain for different pressures has been calculated adopting analytical track structure calculations. The propane gas gain results always higher than the dimethyl ether (DME) one for each investigated pressure. Monte Carlo simulations carried out with an ad hoc track structure code show that the avalanche statistics has a minor role in the acquired distribution and suggest that this TEPC is able in reproducing nanodosimetric distributions of alpha particles for simulated site sizes of some tenths of nanometers. Highlights: Avalanche-confinement TEPC able to simulate site sizes down to nanometric region. Direct comparison between track-nanodosimetry and microdosimetry. The TEPC reproduces track-nanodosimetry Monte Carlo simulations.